More tell me why; answers to over 400 questions children ask most often. - Leokum, Arkady; Koehler, Cynthia Iliff; Koehler, Alvin (New York, Reed Childrens, 2000)
An encyclopedic collection of questions and answers about nature, man, inventions, and customs.
Keywords: Children's questions and answers -- Juvenile literature; Questions and answers